Notes on the races, castes and trades of Eastern Bengal - Wise, James, author.
1 online resource (542 pages)
Keywords: James Wise was Civil Surgeon of Dacca for ten years and in that capacity had great opportunities of observing the social life of the people of Bengal. During his stay there he collected material for a book which he published in 1883 after his retirement under the title Notes on the Races, Castes, and Trades of Eastern Bengal. It was printed by Her Majestry's printer Harrison and Sons', St. Martin Lane, London. Only 12 copies were originally printed. A doctor by profession and an anthropologist by vocation, the erudition and companionship of Wise even made the visit of the famous archaeologist Alexander Cunningham to Sonargaon and Vikrampur fruitful. The Wiseghat' on the bank of river Buri Ganga was named after him. James Wise died in July 1885. The present volume is a reprint of the above noted book on colonial Bengal by James Wise. It is divided into five parts, viz, Muhammadan', Religious Sects of the Hindus', Hindu Castes and Aboriginal Races', Armenians' and Portuguese in Eastern Bengal'. The present edition has been reset and contains a comprehensive introduction by the editor. It places the volume in context and explains the relevance of the work for the present times. The volume will be invaluable for scholars of colonial, cultural and anthropological history of Bengal.